1992
DOI: 10.1111/j.1469-7610.1992.tb00873.x
|View full text |Cite
|
Sign up to set email alerts
|

Attention Deficit and Reading Achievement

Abstract: A model for estimating possible reciprocal relationships between attention deficit and reading achievement is proposed. This model is fitted to data for a birth cohort of New Zealand children studied at 10 and 12 years on measures of attention deficit and reading achievement. Model estimates suggest that at the age of 12 years the predominant direction of causality is that attention deficits influence reading achievement and there is no evidence to suggest that reading achievement influenced attention deficit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
33
0
3

Year Published

2000
2000
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(41 citation statements)
references
References 15 publications
5
33
0
3
Order By: Relevance
“…Wood and Felton (1994) found that attention disorder had no measurable impact on word decoding; Fergusson and Horwood (1992) reported a contrary result. It is widely believed that attention difficulties have their primary impact on comprehension (Schulte, et al, 1999).…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Wood and Felton (1994) found that attention disorder had no measurable impact on word decoding; Fergusson and Horwood (1992) reported a contrary result. It is widely believed that attention difficulties have their primary impact on comprehension (Schulte, et al, 1999).…”
Section: Introductionmentioning
confidence: 96%
“…Estimates of the overlap range from 10 to 20% (Hinshaw, 1992) to 20 to 40% (DuPaul & Stoner, 1994). Although it can be argued that attention disorders and reading disabilities result from separate sets of cognitive deficits--phonological processing for reading disabilities and executive functioning deficits for attention disorders (Pennington, 1991)--attention disorders may make it more difficult for a child to learn to read, thereby causing the child to exhibit poor reading performance (Fergusson & Horwood, 1992;Rabiner & Coie, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…και βασίζεται εν μέρει στο θεωρητικό μοντέλο των Bar-On & Parker (2000), το οποίο αποτελείται από τις πέντε παραπάνω υποκλίμακες. Η υποκλίμακα των προβλημάτων συμπεριφοράς περιλαμβάνει διαπροσωπικές και ενδοπροσωπικές δεξιότητες, στην ύπαρξη των οποίων έχουν αναφερθεί οι Handwerk and Marshall (1998), καθώς και υπερκινητικότητα και δυσκολίες συγκέντρωσης (Ferguson & Horwood, 1992). Η Κλίμακα εκπαιδευτικών για την ψυχοκοινωνική προσαρμογή (Χατζηχρήστου κ. ά., 2008), δόθηκε στους εκπαιδευτικούς των αντίστοιχων παιδιών για να τη συμπληρώσουν.…”
Section: συμμετέχοντεςunclassified
“…Children in poverty tend to have lower attention skills than their more advantaged peers (Mezzacappa, 2004), which contributes to lower academic achievement (Breznitz & Norman, 1998;de Jong, 1993;Fergusson & Horwood, 1992). A recent study by Blair and Razza (2007) shows that the attentional skills of children living in poverty impact their math and literacy achievement.…”
Section: Potential Implicationsmentioning
confidence: 99%
“…The link between attention skills and causal understanding is suggested by research with children diagnosed with ADHD (Lorch, O'Neil et al, 2004;Lorch, Diener et al, 1999;Lorch, Sanchez et al, 1999) and research showing relations between attention and school achievement, in particular reading achievement Rabiner, Coie, & The Conduct Problems Prevention Research Group, 2000;Rapport, Scanlan, & Denney, 1999;de Jong, 1993;Fergusson & Horwood, 1992). No study has examined how the attention of children without diagnosed attention deficits influences causal understanding.…”
Section: Introduction 1 Introductionmentioning
confidence: 99%